2006
DOI: 10.1542/peds.2006-1846
|View full text |Cite
|
Sign up to set email alerts
|

Asthma as a Barrier to Children's Physical Activity: Implications for Body Mass Index and Mental Health

Abstract: We found that children attending a hospital clinic for asthma were more likely to be obese and were significantly less active than a comparison group with other medical conditions. Asthma was identified as a barrier to exercise by parents and children. Strategies to promote exercise within pediatric asthma care are needed to protect both mental and physical health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
144
2
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(157 citation statements)
references
References 38 publications
5
144
2
6
Order By: Relevance
“…8,9 Research has confirmed the link between parents' perceptions of risk and physical activity levels in their children. 9 A US study of 137 parents found that children whose parents believed that the child would become ill from exercise were more likely to be inactive.…”
Section: Comparison With Existing Literaturementioning
confidence: 95%
See 1 more Smart Citation
“…8,9 Research has confirmed the link between parents' perceptions of risk and physical activity levels in their children. 9 A US study of 137 parents found that children whose parents believed that the child would become ill from exercise were more likely to be inactive.…”
Section: Comparison With Existing Literaturementioning
confidence: 95%
“…5 However, it has specific benefits for children with asthma, including reduced hospital admissions, reduced school absenteeism, fewer consultations with GPs, reduced medication, 6 and improved ability to cope with asthma. 7 Despite these benefits, rates of physical activity among young people with asthma are lower than their nonasthmatic peers, [8][9][10][11][12] and are continuing to decline as rates fall more generally among young people in most industrialised nations. 13,14 Three interconnected factors affect participation in physical activity by children with asthma: the illness beliefs of young people; 15,16 parental and family beliefs; 9,17 and the knowledge of teachers and organisational arrangements in schools.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies showed that children who wheezed were less physically active than children who did not wheeze. [20][21][22] By contrast, others did not find such association 9 or even found the reverse. 23 Because these studies were cross-sectional in design, they provide no information about the direction of the association.…”
mentioning
confidence: 88%
“…Asthma not only increases school absenteeism and fears, but it also decreases physical activity for children with asthma. Glazebrook et al (2006) reported that two-thirds of children with asthma stated that asthma stopped them from doing sports and limited their activity based on reports of an average of two fewer activities per day than children without asthma, (4 activities per day vs. 6 activities per day). For parents of children with asthma a decreased quality of life is related to missed workdays, limited activities, inadequate sleep, frequent night awakenings and decreased emotional health.…”
Section: Introductionmentioning
confidence: 99%